Natalizumab treatment of multiple sclerosis: new insights. - Delbue, Serena; Comar, Manola; Ferrante, Pasquale (Immunotherapy, 2017)
Natalizumab is a monoclonal antibody directed against the α4 chain of the very late activating antigen 4 and α4β7 integrins, present on the leukocytes surface, used as monotherapy for the treatment of relapsing-remitting multiple sclerosis. It substantially reduces relapse rate and the accumulation of disability, but its use is associated with a very adverse event, that is the development of progressive multifocal leukoencephalopathy, a fatal demyelinating disease of the CNS, due to the lytic replication of the human polyomavirus JC. The main focus of the review is to describe the newest insights on natalizumab, its current use in the clinical practice, the natalizumab-treated patients' management and the risk stratification related to the progressive multifocal leukoencephalopathy development.
Keywords: Animals; Drug-Related Side Effects and Adverse Reactions; Humans; Immunotherapy; Integrin alpha Chains; Integrin alpha4; Integrin beta Chains; JC Virus; Leukoencephalopathy, Progressive Multifocal; Multiple Sclerosis, Relapsing-Remitting; Natalizumab; Risk; Virus Activation; Virus Replication